Development of newly synthesised quinazolinone-based CDK2 inhibitors with potent efficacy against melanoma - Eman R. Mohammed; Ghada F. Elmasry (Taylor & Francis Group, 2022)
Inhibiting Cyclin-dependent kinase 2 (CDK2) has been established as a therapeutic strategy for the treatment of many cancers. Accordingly, this study aimed at developing a new set of quinazolinone-based derivatives as CDK2 inhibitors. The new compounds were evaluated for their anticancer activity against sixty tumour cell lines. Compounds 5c and 8a showed excellent growth inhibition against the melanoma cell line MDA-MB-435 with GI% of 94.53 and 94.15, respectively. Cell cycle analysis showed that compound 5c led to cell cycle cessation at S phase and G2/M phase revealing that CDK2 could be the plausible biological target. Thus, the most cytotoxic candidates 5c and 8a were evaluated in vitro for their CDK2 inhibitory activity and were able to display significant inhibitory action. The molecular docking study confirmed the obtained results. ADME study predicted that 5c had appropriate drug-likeness properties. These findings highlight a rationale for further development and optimisation of novel CDK2 inhibitors.